2020
DOI: 10.1007/s13239-020-00476-w
|View full text |Cite
|
Sign up to set email alerts
|

A Percutaneous Catheter for In Vivo Hyperspectral Imaging of Cardiac Tissue: Challenges, Solutions and Future Directions

Abstract: Multiple studies have shown that spectral analysis of tissue autofluorescence can be used as a live indicator for various pathophysiological states of cardiac tissue, being it ischemia, ablationinduced damage or scar formation. Yet today there are no percutaneous devices that can detect autofluorescence signals from inside a beating heart. Multiple surgical interventions can benefit from the development of such a device. It can help to reduce recurrence rates of atrial fibrillation ablation procedures by in-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Compared to UVB or UVC, the UVA exposure causes the least damage due to its longer frequency which translates to lower photon energy. Secondly, our recent quantitative analysis 16 has shown that the levels of UV needed for percutaneous Auf-HSI imaging are well below the established thresholds that can damage the skin. Lastly, the layer of endocardial collagen essentially shields the underlying muscle cells from direct UV exposure further minimizing any potential damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to UVB or UVC, the UVA exposure causes the least damage due to its longer frequency which translates to lower photon energy. Secondly, our recent quantitative analysis 16 has shown that the levels of UV needed for percutaneous Auf-HSI imaging are well below the established thresholds that can damage the skin. Lastly, the layer of endocardial collagen essentially shields the underlying muscle cells from direct UV exposure further minimizing any potential damage.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions and the shape of the lesions delineated by Auf-HSI were in perfect agreement with the conventional post-ablation staining methods such as TTC [10][11][12][13][14] . These promising bench findings have led to our ongoing efforts to incorporate Auf-HSI technology into a percutaneous imaging catheter 11,15,16 . The design of this catheter includes a saline-filled balloon to displace optically dense blood from the endocardial surface.…”
mentioning
confidence: 99%
“…OCT-integrated catheters enabled real-time imaging feedback to identify tissue structures and direct monitoring of RF lesion formation, ex vivo 19 , 22 24 and in vivo 15 , 25 . Recently, acute necrotic areas in atrial tissue were identified using hyperspectral imaging system based on ultraviolet-excited tissue autofluorescence 11 , 26 28 . Another promising technique, near-infrared spectroscopy (NIRS), uses broadband light to interrogate tissue volumes deeper than OCT and ultraviolet-excited tissue autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In the latter case, optically dense blood must be displaced from an optical path, either by influx of saline or via an inflatable balloon. 21,22 Such balloons must exhibit minimal levels of fluorescence within optical ranges of biological fluorophores. Otherwise, they can diminish Auf-HSI's ability to reveal the target tissue due to inherent autofluorescence of their material.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 In the latter case, optically dense blood must be displaced from an optical path, either by influx of saline or via an inflatable balloon. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%